Application of Lateral Crater Test in Open Pit Blasting Parameters Optimisation - Y M. Wang; W Z. Liu; X L. Zhang; L F. Li (The Australasian Institute of Mining and Metallurgy, 2015)
Based on the blasting crater theory, the equation between k under typical cases and burden line, charge height was obtained by open pit bench blasting analysis model. The model was calculated with mine production blasting. The blastability coefficient k and the best range of blasting burden line were specially emphasised on determination of lateral crater tests.CITATION:Wang, Y M, Liu, W Z, Zhang, X L and Li, L F, 2015. Application of lateral crater test in open pit blasting parameters optimisation, in Proceedings 11th International Symposium on Rock Fragmentation by Blasting, pp 463–468 (The Australasian Institute of Mining and Metallurgy: Melbourne).